The influence of entrepreneurial supports on business performance among rural entrepreneurs - Mohd Zin, Md. Lazim; Ibrahim, Hadziroh (International Association of Educators and Researchers (IAER), 2020)
The present study attempts to provide empirical evidence on the relationship between the four facets of entrepreneurial supports and rural entrepreneurs business performance. The entrepreneurial supports considered in the study are entrepreneurship training, marketing support, business networking, and financial support. A survey among 183 rural entrepreneurs was carried out. Self-reported measures were used to obtain data pertaining to government entrepreneurial initiatives and rural entrepreneurs’ business performance. The multiple regression analysis was used to ascertain the proposed relationships and it was found that all entrepreneurial initiatives such as entrepreneurship training, marketing support, business networking and financial support were significantly related to business performance. Discussion on the findings is highlighted, so as the implications for practice and future research. Towards the end, the paper also highlights limitations of the study that could be taken into consideration by future scholars for further empirical enrichment.